Hybrid microfluidic herringbone mixer for tangential flow filtration - Goh, Kelly Jia Yi (Nanyang Technological University, 2024)
Extracellular vesicles (EVs) serve as crucial mediators of intercellular communication, carrying disease-specific cargo such as proteins and nucleic acids, making them promising biomarkers for various diseases in clinical diagnostics. However, the complexity of current EV isolation methods poses challenges for clinical adoption, highlighting the need for more efficient solutions. A key challenge is the presence of the plasma proteins which require additional methods in order to deplete them from EVs prior to EV analysis. For effective EV filtration, tangential flow filtration (TFF), a method of isolation that passes fluids across a membrane is employed. Micromixers are devices that use mechanical components to induce mixing. Mixing of fluids in laminar flow within microchannels is limited due to diffusive mixing , which compromises filtration efficiency and accuracy of downstream analysis.